Macrophages are essential for CTGF-mediated adult β-cell proliferation after injury - Kimberly G. Riley; Raymond C. Pasek; Matthew F. Maulis; Jennifer C. Dunn; W. Reid Bolus; Peggy L. Kendall; Alyssa H. Hasty; Maureen Gannon (Elsevier, 2015)
Objective: Promotion of endogenous β-cell mass expansion could facilitate regeneration in patients with diabetes. We discovered that the secreted protein CTGF (aka CCN2) promotes adult β-cell replication and mass regeneration after injury via increasing β-cell immaturity and shortening the replicative refractory period. However, the mechanism of CTGF-mediated β-cell proliferation is unknown. Here we focused on whether CTGF alters cells of the immune system to enhance β-cell replication. Methods: Using mouse models for 50% β-cell ablation and conditional, β-cell-specific CTGF induction, we assessed changes in immune cell populations by performing immunolabeling and gene expression analyses. We tested the requirement for macrophages in CTGF-mediated β-cell proliferation via clodronate-based macrophage depletion. Results: CTGF induction after 50% β-cell ablation increased both macrophages and T-cells in islets. An upregulation in the expression of several macrophage and T-cell chemoattractant genes was also observed in islets. Gene expression analyses suggest an increase in M1 and a decrease in M2 macrophage markers. Depletion of macrophages (without changes in T cell number) blocked CTGF-mediated β-cell proliferation and prevented the increase in β-cell immaturity. Conclusions: Our data show that macrophages are critical for CTGF-mediated adult β-cell proliferation in the setting of partial β-cell ablation. This is the first study to link a specific β-cell proliferative factor with immune-mediated β-cell proliferation in a β-cell injury model.